The Prevalence of Post-traumatic Stress Disorder Symptoms, Sleep Problems, and Psychological Distress Among COVID-19 Frontline Healthcare Workers in Taiwan - Lu, Mei-Yun; Ahorsu, Daniel Kwasi; Kukreti, Shikha; Strong, Carol; Lin, Yi-Hsuan; Kuo, Yi-Jie; Chen, Yu-Pin; Lin, Chung-Ying; Chen, Po-Lin; Ko, Nai-Ying; Ko, Wen-Chien (Frontiers in Psychiatry, 2021)
The adverse effect of COVID-19 pandemic among individuals has been very disturbing especially among healthcare workers. This study aims to examine the prevalence of posttraumatic stress disorder (PTSD) symptoms, sleep problems, and psychological distress among COVID-19 frontline healthcare workers in Taiwan. Hence, a total of 500 frontline healthcare workers were recruited to participate in this cross-sectional study. They responded to measures on fear of COVID-19, depression, anxiety, stress, insomnia, PTSD, perceived stigma, and self-stigma. The results indicated a prevalence rate of 15.4% for PTSD symptoms, 44.6% for insomnia, 25.6% for depressive symptoms, 30.6% for anxiety symptoms, and 23.4% for stress among the participants. There were significantly positive interrelationships between all these variables. Anxiety symptoms and fear of COVID-19 predicted PTSD whereas symptoms of anxiety, fear of COVID-19, and stress predicted insomnia. The prevalence rates of the psychological problems reveal a worrying view of mental health challenges among Taiwanese frontline healthcare workers. Anxiety symptoms and fear of COVID-19 are the common predictive factors of PTSD and sleep problems suggesting that mental healthcare services for them may help prevent future occurrence of psychological problems by allaying fears of healthcare workers. Therefore, there should be mental healthcare services for healthcare workers during the COVID-19 pandemic.